Mechanische und metabolische Belastung beim Radfahren - eine Analyse aus physiologischer und biomechanischer Sicht - Beneke, R.; Di Prampero, P. E. (Deutsche Zeitschrift für Sportmedizin, 2001)
Bicycle riding has been booming during recent years utilizing the bike as sports kit for leisure time recreational and top performance exercises or simply as a reasonable vehicle in daily life. This enthusiasm is essentially based on the fact that at a given velocity cycling needs less metabolic power than any other terrestial muscle-powered mode of human locomotion. In the present paper cycling is described and analysed as a complex model of performance limiting factors with special respect to physiology and biomechanics. The model includes cycling velocity (v), rolling resistance (C R ) and resistances against gravity (C G ) as body mass related factors of physical strain (a = C R + C G ) but also air resistance (C L = b (v + v L cos . ) 2 ) considering wind velocity (v L ) and wind direction (. ). The parameter b subsumes drag coefficient agianst air, area projected on the frontal plane and air density. The metabolic power results from biomechanical efficiency (ç ) and mechanical power (P Mech ) based on interrelationships described above (P Met = P Mech ç -1 = (C R + C G + C L ) v ç -1 = (a + b (v + v L cos . ) 2 ) ç -1 ). The model enables calculation of energy cost of cycling and thus performance limitations with respect to physical fitness under various conditions which makes optimized prescription of exercise training possible.